State transitions of a confined actomyosin system controlled through contractility and polymerization rate - Ryota Sakamoto; Makito Miyazaki; Yusuke T. Maeda (Physical Review Research, 2023)
Pattern formation induced by symmetry breaking is a fundamental concept underlying biological phenomena across different scales, from single cells to tissues. However, the mechanics behind the pattern formation of the actomyosin system remains elusive due to complex biochemical regulations in living cells. In this study, we report the transition between distinct patterns of cytoplasmic actomyosin networks: steady actin flow and periodic actin waves, which are confined to a quasi-two-dimensional cell-like compartment. By combining molecular perturbations and numerical simulations of the active fluid model, we show that contractility and actin polymerization rate are the critical factors for the state transition from the steady actin flow to periodic actin waves. These patterns emerge either when active stress outweighs the diffusive relaxation of actin filaments or when the actin polymerization rate is sufficiently slow to accumulate actin filaments close to the surface of the circular confinement. Furthermore, our active fluid model predicts that the spatial heterogeneity at the onset of contraction leads to a rotational actin wave, which is stable only at the phase boundary between the steady actin flow and periodic actin waves. This study provides an integrative understanding of the distinct pattern formation of active gels confined in cell-sized spaces.